CLINICAL AND CEPHALOMETRIC ANALYSIS OF THREE CASES WITH PYCNODYSOSTOSIS: CASE REPORTS - DEMİRCİOĞLU, SERAP (ISTANBUL UNIV PRESS, ISTANBUL UNIV RECTORATE, 2015)
The aim of this article is to present intra-and extra-oral and cephalometric findings of three patients with a rare disease: the pycnodysostosis. Two cases had skeletal Class III malocclusion due to maxillary retrognathia and one had bimaxillary retrusion with Class I relationship. Total circular crossbite, increased gonial angle and vertical facial proportions, deep-narrow palates and retruded upper lip were found in all cases. Maxillary expansion, face mask treatment or/and orthognathic surgery are treatment alternatives, considering the growth and development. Bone fragility and the risk of osteomyelitis after extractions should be considered in such cases before orthodontic treatment and orthognatic surgery.
Keywords: Pycnodysostosis; clinical evaluation; cephalometric evaluation